Unplanned 180-day Readmissions and Health Care Utilization after Immediate Breast Reconstruction for Breast Cancer - Rios-Diaz, Arturo J.; Habarth-Morales, Theodore E.; Isch, Emily L.; Amro, Chris; Davis, Harrison D.; Broach, Robyn B.; Jenkins, Matthew; Fischer, John P.; Serletti, Joseph M. (Journal of Reconstructive Microsurgery, 2024)
To assess the burden of postdischarge health care utilization given by readmissions beyond 30 days following immediate breast reconstruction (IBR) nationwide.Women with breast cancer who underwent mastectomy and concurrent IBR (autologous and implant-based) were identified within the 2010 to 2019 Nationwide Readmission Database. Cox proportional hazards and generalized linear regression controlling for patient- and hospital-level confounders were used to determine factors associated with 180-day unplanned readmissions and incremental hospital costs, respectively.Within 180 days, 10.7% of 100,942 women were readmitted following IBR. Readmissions tended to be publicly insured (30.8 vs. 21.7%, p < 0.001) and multimorbid (Elixhauser Comorbidity Index > 2 31.6 vs. 19.6%, p < 0.001) compared with nonreadmitted patients. There were no differences in readmission rates among types of IBR (tissue expander 11.2%, implant 10.7%, autologous 10.8%; p > 0.69). Of all readmissions, 40% occurred within 30 days and 21.7% in a different hospital and 40% required a major procedure in the operating room. Infection was the leading cause of readmissions (29.8%). In risk-adjusted analyses, patients with carcinoma in situ, publicly insured, low socioeconomic status, and higher comorbidity burden were associated with increased readmissions (all p < 0.05). Readmissions resulted in additional $8,971.78 (95% confidence interval: $8,537.72–9,405.84, p < 0.001) in hospital costs, which accounted for 15% of the total cost of IBR nationwide.The majority of inpatient health care utilization given by readmissions following mastectomy and IBR occurs beyond the 30-day benchmark. There is evidence of fragmentation of care as a quarter of readmissions occur in a different hospital and over one-third require major procedures. Mitigating postoperative infectious complications could result in the highest reduction of readmissions.
Keywords: breast cancer; mastectomy; immediate breast reconstruction; unplanned readmission; costs; epidemiology; health care utilization; nationwide